Evaluation of the book and periodical collections of the College of Allied Medical Professions - De Leon, Rosa I.; Faderon, Rosalie B.; Rosal, Rosvida R.; Arellano, Clarita A. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2003)
The College of Allied Medical Professions, University of the Philippines was the first school in the Philippines to offer the Bachelor of Science degree in Occupational Therapy, Physical Therapy, Speech Pathology, Masters in Clinical Audiology and Masters in Rehabilitation Science. In its 40 years of existence, the College has always maintained a quality of standards in its graduates who are unparalleled in the practice of their future profession. The professions must provide a vast amount of knowledge for each student. This basic theoretical knowledge must be translated into the practical clinical setting in which all students must go through. Through the College's 39 years of servicing the Filipino public, the College Library has been at the forefront in providing the necessary, adequate, well-selected and organized information for its major clientele, which includes students, faculty, researchers and other users. The College Library is an essential source of information for the intellectual advancement in the health sciences.
This study evaluated the library collections, namely the periodical and book sections qualitatively and quantitatively. It determined the strength and weaknesses of the collection through a descriptive comparison of the collection of the College Library in relation to two foreign institutions that have similar objectives. The study compared the collection to the Brandon-Hill List that is the standard list used by health libraries as basis for the contents of their collections. It also compared the College Library standards to the University of the Philippines Library standards. Lastly, it evaluated the Library collection according to the perceptions of the faculty and students. The main areas focused on the recency, adequacy and comprehensiveness of the collection.
The results of the study may serve as guidelines in the planning and formulation of the Library's collection development program. One hundred twenty-three respondents (123) were asked to answer the questionnaires. There was (100 response rate, which may be attributed to the method of data gathering. The average age of the respondents is 22.7. Around (68 of the respondents are females while (32 are males. More than half (55 of the sample came from the undergraduate level, while almost 20 percent came from the faculty. A little over 16 percent of the sampled library users were alumni. The top four (4) purposes if visiting the library was research (109) borrowing and returning library materials (90), studying (58), and leisure reading (49). Other purposes noted by the respondents were using the computer and Internet, along with conducting group discussions and meetings. An assessment of the standard by UP System for UP Libraries revealed that the book collection of the UP CAMP :Library does not meet the set standards. UP CAMP only meets around 53 percent of the total volume of books required. On the other hand, the current listing of UP CAMP periodicals exceeds the requirement of 50 titles for a student population of less than 1000. It can be noted from the graph that the University of the Philippines College of Allied Medical Professions Library collections are greater in number compared to University of Queensland and University of South Alabama in all categories, Occupational therapy, Physical therapy, Speech Pathology and the journals. The University of Queensland was second, and the University of South Alabama had the least amount of materials in all categories listed. Overall, the University of the Philippines, College of Allied Medical Professions Library had the largest collection of 1624 followed by the University of Queensland at 1179. The University of South Alabama had the smallest overall collection at 400. This comparison was done without regard to the Brandon/Hill List of recommended books and periodicals. Furthermore, the UP-CAMP library has in its acquisition 63 percent of the selected Brandon/Hill List of printed books and journals in allied health , while University of Queensland has only acquired 43 percent of those materials suggested in the Brandon/Hill List. The University of South Alabama had the lowest percentage of acquired materials in the Brandon/Hill List at 31 percent. Recommendations based on the gathered information and analyses: that the CAMP Library collection be maintained, and more books be added to continually be at par with the other institutions with the same specialization and to fulfill the standards set by the university and international boards.
Vita.
Special Problem (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines (Manila). -- College of Allied Medical Professions. Library -- Evaluation; Medical libraries -- Collection development -- Evaluation. -- Philippines -- Manila